4-H Livestock Judging: Activity 1, Parts is Parts - Chad Carr; Justin Crosswhite; Amanda Jhonson (EDIS)
This document is an educational guide. It serves as a curriculum resource within the Florida 4-H program, specifically designed for teaching livestock judging to young people aged 11-18. The guide emphasizes the development of various life skills through judging activities, such as communication, decision making, and organizational skills, while also aiming to boost confidence and self-esteem among participants. The document is intended for 4-H leaders and coaches, providing encouragement and guidance for those who may lack extensive background knowledge in animal science. It highlights the importance of animal science within the Florida 4-H educational framework and underscores the positive impact of livestock judging programs on youth development. The guide also aims to reassure and support potential leaders, emphasizing that successful programs can be led effectively without requiring advanced subject matter expertise. Original publication date November 1992.